Local legitimacy and international peacebuilding - Richmond, Oliver P.; Mac Ginty, Roger, 1970- (Edinburgh University Press, 2020)
"This edited volume focuses on disentangling the interplay of local peacebuilding processes and international policy, via comparative theoretical and empirical work on the question of legitimacy and authority. Using a number of conflict-affected regions as case studies - including Kosovo, Iraq, Bosnia-Herzegovina and Sudan - the book incorporates the expertise of a range of international scholars in order to understand the dynamics of local peacebuilding, the construction of legitimate authority, and its interplay with internationally led peace- and state-building interventions. The commissioned chapters advance our understanding of local legitimacy, sustainable international engagement, and the hybrid forms of authority they produce."--Publisher's description